2021
DOI: 10.1007/s11063-021-10555-1
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lightweight Deep Learning-Based Histopathological Image Classification Model for IoMT

Abstract: The unavailability of appropriate mechanisms for timely detection of diseases and successive treatment causes the death of a large number of people around the globe. The timely diagnosis of grave diseases like different forms of cancer and other life-threatening diseases can save a valuable life or at least extend the life span of an afflicted individual. The advancement of the Internet of Medical Things (IoMT) enabled healthcare technologies can provide effective medical facilities to the population and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…(a) Utilizing various CNN algorithms for feature extraction from medical images [69], and (b) A hybrid approach that merges using a mathematical formula [70].…”
Section: Ensemble Methodsmentioning
confidence: 99%
“…(a) Utilizing various CNN algorithms for feature extraction from medical images [69], and (b) A hybrid approach that merges using a mathematical formula [70].…”
Section: Ensemble Methodsmentioning
confidence: 99%
“…Model training is resource-intensive and timeconsuming, underscoring the importance of well-trained models to avoid inaccurate predictions with low probabilities. The integration of CNN principles into breast cancer detection elevates diagnostic accuracy and introduces a sophisticated and adaptable approach to healthcare [25]. This approach facilitates efficient pattern recognition and predictions within the dynamic landscape of medical data, marking a substantial advancement in diagnosing and managing breast cancer in humans [26][27][28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies demonstrated that although CNNs with greater scale or depth were able to result outstanding classification performance, they often have a significant drawback in execution time ( 9 , 14 - 16 ). Several lightweight architectures were proposed to address the drawback, which at the same time, able to yield a noticeable high accuracy (Acc) at a low latency ( 17 - 20 ).…”
Section: Introductionmentioning
confidence: 99%